Relationship between need supply major fit and demand ability major fit with academic achievement - Vahidi, Naghmeh; Roslan, Samsilah; Chong Abdullah, Maria; Omar, Zoharah (American Research Institute for Policy Development, 2016)
Recently, despite the high budget that has been allocated for education in Malaysia, the educational performance among students remains low (Blueprint, 2013). Pascarella and Terenzini (2005; 1991) have identified four theories and models that affect students’ learning, namely; (a) psychosocial, (b) cognitivestructural, (c) typological, and (d) person-environment interaction. This study focuses on the effects of person-environment interaction on academic achievement. The interactionist approach emphasizes that, neither personal characteristics nor situational factors alone are able to identify the attitudes or responses of people, but the interaction between them can be highly influential (Schneider, 1982; Terborg, 1981). Personenvironment fit arguments were raised by interactionists who discussed that particular attitudes, behaviours and cognitions are the results of the interaction between situational factors and individuals (Chatman, 1989; Muchinsky & Monahan, 1987; Ostroff & Schulte, 2007). The present study used academic achievement that is one of the outcomes of person–environment (P–E) fit. This research employed different types of P-E fit such as, objective and perceived interest major fit. The main aim of the present study was to examine the relationship between the P-E fit and academic achievement. The study was carried out in University Putra Malaysia (UPM). The participants of the study included 2503 undergraduate students from 12 different faculties of UPM. The findings for the relationship between P-E fit and academic achievement revealed that there was a positive significant relationship between need supply major fit and demand ability major fit with academic achievement.